THE FUTURE OF VILLAGE DEVELOPMENT IN THE HANDS OF NEW LEADERS - Septimawan Sutopo, Dhanny (PT. Intelek Cendikiawan Nusantara, 2024)
In this article, we explore the future vision of village development on the transition of power. How is the concept of